Development of acoustic nonwoven materials from kapok and milkweed fibres. Issue 4 (2nd April 2016) - Ganesan, P.; Karthik, T.
Abstract : Acoustic properties of textile materials have been studied for several decades. But, mostly used materials were synthetic, and hence, they were not eco-friendly in nature. Therefore, an attempt was put forward to try the sound absorption property of natural fibres and their blends by needle-punched nonwoven techniques. Nonwoven fabrics of ideal materials are used as acoustical insulation products because they have high total surface area. The effect of blend proportion of kapok and milkweed fibres with cotton, fabric GSM, bulk density and distance of fabric from sound source on sound reduction of nonwoven fabrics was investigated. The sound reduction increases with increase in blend proportion of kapok and milkweed fibres. A nonwoven fabric of cotton/milkweed 40/60 shows the highest sound reduction potential. As the distance between the fabric and sound sources increases, the sound reduction also increases linearly due to reduction of sound intensity which reduces the transmission of sound through the fabric. There is a positive correlation between fabric GSM and sound reduction and negative correlation between bulk density and sound reduction. Further, the thermal conductivity of nonwoven samples decreases with increase in kapok and milkweed blend proportion due to increase in thickness of samples. Hence, the kapok- and milkweed-blended nonwoven samples provide sound as well as thermal insulation characteristics.